PENGARUH PARTISIPASI PEMAKAI TERHADAP KEPUASAN PEMAKAI DALAM PENGEMBANGAN SISTEM INFORMASI AKUNTANSI DENGAN KOMPLEKSITAS TUGAS DAN KOMPLEKSITAS SISTEM SEBGAI VARIABEL MODERATING (Studi Empiris Pada Perusahaan Manufaktur di Magelang) - M Al Al; Dian Rais Rais (Jurnal Analisis Bisnis Ekonomi, 2016)
This research aim to test influence of user participation to satisfaction of user which is dimoderasi by duty complexity and system complexity in development of accounting information system. Accountancy information system in resource corps had company to yield information required by internal side and eksternal, one of the yielded output in the form of information concerning processed financial statement of monetary transaction datas. Considering important role and existence of accounting information system. In change of accounting information system of manual system become computerization system [do] not only concerning change of technology but also change of behavior, is there for needed by existence of participation of user.